2017
DOI: 10.1021/acsami.6b15587
|View full text |Cite
|
Sign up to set email alerts
|

Transparent, Flexible Piezoelectric Nanogenerator Based on GaN Membrane Using Electrochemical Lift-Off

Abstract: A transparent and flexible piezoelectric nanogenerator (TF PNG) is demonstrated based on a GaN membrane fabricated by electrochemical lift-off. Under shear stress on the TF PNG by finger force (∼182 mN), the GaN membrane effectively undergoes normal stress and generates piezoelectric polarization along the c-axis, resulting in the generation of piezoelectric output from the TF PNG. Although the GaN layer is 315 times thinner than the flexible polyethylene terephthalate (PET) substrate, the low Young's modulus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 32 publications
0
37
0
Order By: Relevance
“…This suppresses the carrier screening effect and enhances the output voltage. Kang et al (2017) demonstrated the transfer of a large area GaN membrane onto a flexible PET substrate in a transparent flexible piezoelectric nanogenerator using electrochemical lift-off process resulting in an output voltage and current of 4.2 v and 150 nA [53]. The same electrochemical lift-off process was used by Johar et al to fabricate a flexible PENG by forming a p-n NiO/GaN heterojunction [54].…”
Section: Nanogenerators Based On Piezoelectric Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…This suppresses the carrier screening effect and enhances the output voltage. Kang et al (2017) demonstrated the transfer of a large area GaN membrane onto a flexible PET substrate in a transparent flexible piezoelectric nanogenerator using electrochemical lift-off process resulting in an output voltage and current of 4.2 v and 150 nA [53]. The same electrochemical lift-off process was used by Johar et al to fabricate a flexible PENG by forming a p-n NiO/GaN heterojunction [54].…”
Section: Nanogenerators Based On Piezoelectric Effectmentioning
confidence: 99%
“…The first PENG was based on ZnO nanowires, and there were several improved models with ZnO nanowires. Apart from these, various other 1D nanomaterials like CdS, GaN, ZnS, InN, CdSe, InAs and 2D MoS 2 that have good piezoelectric potential were also studied [25,30,31,53,55,82,83]. Optimization of structural design, integration, and packing of nanogenerators for self-powered sensors are some of the future requirements that have to be addressed for efficient electromechanical energy conversion.…”
Section: Nanogenerators Based On Piezoelectric Effectmentioning
confidence: 99%
“…In order to harvest high piezoelectric output from a semiconductor PG, suppression of internal screening by rectifying contact is an essential requirement. Forming a p-n homojunction and heterojunction is an efficient route to harvest high piezoelectric output by suppressing the free carrier screening and junction screening [ 20 , 21 , 22 , 23 , 24 ]. Until now, most of the PNGs that are based on GaN NWs have been constructed using Schottky junction configuration, as in the case of resiscopy [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Inorganic materials such as metals, functional metals, semiconductors, oxides and ceramics can be deposited via DC/RF plasma sputtering onto flexible substrates, but it is unclear how the flexible substrate affects their quality and properties relative to the same thin films coated onto traditional solid substrates like glass or Silicon wafers. This is a growing field of research and development and very interesting studies have already been published reporting the deposition of flexible structures for energy harvesting [5], flexile ferroelectric random access memories [6], flexible electroluminescent devices [7], flexible organic ferroelectrics [8], flexible synthetic anti-ferromagnets and nano-wires [9] and flexible solar cells [10]. In this paper we describe the deposition and experimental studies of flexible polycrystalline Ni80Fe20 permalloy thin films, together with a comparison study of their magnetic properties in rigid and flexible forms.…”
Section: Introductionmentioning
confidence: 99%